Student perceptions on the benefits of Flipgrid in a HyFlex learning environment. Issue 6 (18th August 2021) - Keiper, Margaret C.; White, Amanda; Carlson, Cameron D.; Lupinek, Joshua M.
Abstract: Various course delivery methods exist within higher education ranging from face-to-face to HyFlex (hybrid flexible) methods. This research is a mixed method, exploratory study designed to investigate the perceived effectiveness of Flipgrid, an online video discussion board learning tool that can be utilized on a smart phone, in HyFlex delivery modality business courses. A questionnaire containing both Likert-style and open-ended questions was administered to ten unique undergraduate and graduate business courses over a 2-year period. Results indicate that Flipgrid is a beneficial learning tool and further timely research should be conducted with HyFlex courses becoming more prevalent due to COVID-19.